Implementasi Kebijakan Penanganan dan Penyelesaian Sengketa Tanah Melalui Mediasi di Kantor Pertanahan Kota Pekanbaru - W. Muhammad Ramadhani Kurniawan; Masrul Ikhsan (Lembaga Pengembangan Kinerja Dosen, 2025)
The implementation of the Land Dispute Handling and Resolution Policy through Mediation at the Pekanbaru City Land Office has several phenomena such as the number of mediations exceeding the target every year, no change in targets, and a low number of resolutions through mediation. This policy aims to provide legal certainty in order to implement land policy, which is one of the tasks and functions of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency. The purpose of this research is to analyze and describe the Implementation of Land Dispute Handling and Resolution Policy Through Mediation at the Pekanbaru City Land Office. Additionally, it aims to identify the inhibiting factors of the Implementation of Land Dispute Handling and Resolution Policy Through Mediation at the Pekanbaru City Land Office using the Policy Implementation theory according to Van Meter and Van Horn. This research employs a qualitative descriptive research type by collecting data through interviews, observations, and documentation. The results of this study indicate that the Implementation of Land Dispute Handling and Resolution Policy Through Mediation at the Pekanbaru City Land Office has not been carried out effectively due to several shortcomings in various factors. The inhibiting factors include the complexity of synchronizing mediation schedules, inadequate budget, and low mediation success rate.